(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
Whenever I take another look at the Gualdo project, I start remembering all the mistakes that were made. This does not mean that I think the project was wrong in itself, but I reckon that, by some strange alchemical reaction, the series of mistakes produced an architecture that is interesting and pleasant to live in. I am speaking from personal experience: I bought one of the apartments and my family and I spend a large part of our summer holidays there. Things don’t always work out this way, where designers grow to like the houses they have designed; when I paid a visit to the Siedelung Halen in Berne, I found that the architects who had designed it no longer lived in their apartments, preferring to rent them out to tourists and live in normal houses. I wondered if the defects in the Gualdo project cancelled themselves out, like when a flaw in an organism leads to a reaction that produces a capability which compensates for the defect. I prefer to believe, however, that it was the continual changes made to the original design that led to the results we can see today. Would the project have turned out better if we had abided by the original idea, or rather, ideas? We have to take on board the fact that many of the initial ideas were mistaken, and we became aware of this immediately. One of the units of twelve houses (unit H) was built on a provisional basis, as a test case. That being so, we had the means to correct the defects. There is no doubt that certain of the changes, which were carried out at a later stage, were an improvement on the initial design, especially when we could still maintain a degree of control.